Comparative analysis of mathematical equations to estimate leaf area in coffee trees - Schmildt, Edilson Romais; do Amaral, José Augusto Teixeira; Schmildt, Omar; Santos, Jeangelis Silva (Coffee Science - ISSN 1984-3909, 2014)
The measurement of the leaf area is required in many agronomic studies as one of the main parameters to evaluate plant growth. The aim of this work was to select the most appropriate mathematical equation to determine the leaf area of two coffee cultivars Red Catuaí and Catucaí, from their linear leaf dimensions (length, maximum width and length x maximum width), using the equations obtained in this work and the equations cited in the literature. In this work were assessed the models linear, power, circumscribed and exponential that are the most cited in the literature. The results obtained in this study indicate that the simple linear regression and power models equations gives the best estimation of leaf area for the two coffee cultivars ‘Red Catuaí’ and ‘Catucaí’, in the experimental conditions tested.